How Is World Literature Made? The Global Circulations of Latin American Literatures - Müller, Gesine (De Gruyter, 2021)
The debate over world literature, and the underlying questions of global interconnections in a polycentric world, has recently become very visible. Until now, however, the theoretical discussion has lacked material-based approaches to analyze the construction processes of world literature in a transparent fashion. Using Latin American literatures as an example, this volume demonstrates in a tangible way how literature circulates on a global scale.